Comprehensive high-resolution genomic profiling and cytogenetics of two pediatric and one adult medulloblastoma - Holland, Heidrun; Xu, Li-Xin; Ahnert, Peter; Kirsten, Holger; Koschny, Ronald; Bauer, Manfred; Schober, Ralf; Meixensberger, Jürgen; Krupp, Wolfgang (Pathology, research and practice, 2013)
Medulloblastoma (WHO grade IV) is a rare, malignant, invasive, embryonal tumor which mainly occurs in children and represents less than 1% of all adult brain tumors. Systematic comprehensive genetic analyses on medulloblastomas are rare but necessary to provide more detailed information. Therefore, we performed comprehensive cytogenetic analyses (blood and tissue) of two pediatric and one adult medulloblastoma, using trypsin-Giemsa staining, spectral karyotyping (tissues only), SNP-arrays, and gene expression analyses. We confirmed frequently detected chromosomal aberrations in medulloblastoma, such as +7q, −8p/q, −9q, −11q, −12q, and +17q and identified novel genetic events. Applying SNP-array, we identified constitutional de novo losses 5q21.1, 15q11.2, 17q21.31, 19p12 (pediatric medulloblastoma), 9p21.1, 19p12, 19q13.3, 21q11.2 (adult medulloblastoma) and gains 16p11.1-16p11.2, 18p11.32, Yq11.223-Yq11.23 (pediatric medulloblastoma), Xp22.31 (adult medulloblastoma) possibly representing inherited causal events for medulloblastoma formation. We show evidence for somatic segmental uniparental disomy in regions 1p36, 6q16.3, 6q24.1, 14q21.2, 17p13.3, and 17q22 not previously described for primary medulloblastoma. Gene expression analysis supported classification of the adult medulloblastoma to the WNT-subgroup and classification of pediatric medulloblastomas to group 3 tumors. Analyses of tumors and matched normal tissues (blood) with a combination of complementary techniques will help to further elucidate potentially causal genetic events for medulloblastomas.
Gesehen am 17.08.2021